The Effects of Temperature on Microcystin-LR Toxicity to Bosmina Longirostris: Food Web Implications in the Chowan River, North Carolina - Jupitz, Madison C. (East Carolina University, 2017)
In the Chowan River, North Carolina, the frequency of Microcystis aeruginosa blooms has increased over recent years with an average 1.9°C rise in June water temperatures since 1975. Zooplankton are an important trophic link for toxins to move up the food web. Bosmina longirostris, a dominant zooplankton in the Chowan River, consumes toxic M. aeruginosa cells. This study aimed to understand how microcystin-LR, produced from M. aeruginosa blooms, affects B. longirostris mortality under increasing temperatures. B. longirostris were resistant to microcystin-LR, demonstrating an LC50 of 26.3 [mu]g/L. Therefore B. longirostris can survive typical bloom microcystin-LR concentrations ranging less than 0.1 [micro]g/L to 2.0 [mu]g/L. As temperatures were increased from 25°C to 35°C, microcystin-LR mortality increased approximately 18% from 25-27°C; demonstrating that microcystin-LR was more toxic with increasing temperatures. Above 27°C, mortality also increased, but this was due to the effect of temperature rather than increased toxicity of microcystin-LR. This signifies that during spring, when temperatures are below 27°C and B. longirostris are most abundant, microcystin-LR may be most toxic and may have the greatest influence on the Chowan River food web. Under climate change conditions microcystin-LR may eliminate resistant zooplankton from the food web, putting pressure on larval fish and fisheries.
Keywords: Microcystin-LR; Bosmina longirostris; Microcystis aeruginosa--North Carolina; Food chains (Ecology)--North Carolina; Toxicity, Effect of temperature on; Zooplankton--North Carolina; Chowan River (N.C.)